PELATIHAN PEMANFAATAN SISTEM INFORMASI MANAJEMEN DAN PENGAWASANNYA BAGI KARYAWAN PT. ATLANTIC BIRURAYA DENPASAR - Maswari, Ketut Laksmi; Utami Nilawati, Ni Ketut; Dharsika, I Gde Eka (INCIDENTAL : Journal Of Community Service and Empowerment, 2024)
The availability of quality human resources is very important for an organization or company. One of them is management training that can improve organizational effectiveness and efficiency. In this community service that will be carried out is to provide training on the use of management information systems and their supervision. This training activity was carried out at PT. Atlantic Biruraya Denpasar attended by 15 employees, namely one admin head, three admins, one warehouse head, one delivery head, one warehouse checker, two warehouse helpers, three drivers, three delivery helpers. This training activity was held for two days from August 26 2021 to August 27 2021. This training activity manages data into a useful management information system and its supervision. On the first day, material was provided on how to collect and manage data to become an information system and how to supervise the information they have. On the second day, practical activities were carried out on the utilization of management information systems and their supervision.